The Role of Hydrogen Sulfide in Respiratory Diseases - Khattak, Saadullah (Biomolecules, 2021)
Respiratory diseases are leading causes of death and disability around the globe, with a diverse range of health problems. Treatment of respiratory diseases and infections has been verified to be thought-provoking because of the increasing incidence and mortality rate. Hydrogen sulfide (H(2)S) is one of the recognized gaseous transmitters involved in an extensive range of cellular functions, and physiological and pathological processes in a variety of diseases, including respiratory diseases. Recently, the therapeutic potential of H(2)S for respiratory diseases has been widely investigated. H(2)S plays a vital therapeutic role in obstructive respiratory disease, pulmonary fibrosis, emphysema, pancreatic inflammatory/respiratory lung injury, pulmonary inflammation, bronchial asthma and bronchiectasis. Although the therapeutic role of H(2)S has been extensively studied in various respiratory diseases, a concrete literature review will have an extraordinary impact on future therapeutics. This review provides a comprehensive overview of the effective role of H(2)S in respiratory diseases. Besides, we also summarized H(2)S production in the lung and its metabolism processes in respiratory diseases.